Future retreat of Great Aletsch Glacier - Guillaume Jouvet; Matthias Huss (Journal of Glaciology, 2019)
We model the future evolution of the largest glacier of the European Alps – Great Aletsch Glacier, Switzerland – during the 21st century. For that purpose we use a detailed three-dimensional model, which combines full Stokes ice dynamics and surface mass balance forced with the most recent climate projections (CH2018), as well as with climate data of the last decades. As a result, all CH2018 climate scenarios yield a major glacier retreat: Results range from a loss of 60% of today's ice volume by 2100 for a moderate CO2 emission scenario (RCP2.6) being in line with the Paris agreement to an almost complete wastage of the ice for the most extreme emission scenario (RCP8.5). Our model results also provide evidence that half of the mass loss is already committed under the climate conditions of the last decade.